The Influence of Service Quality and Instagram Social Media Promotion on Public Decisions in Choosing Hospitals in West Java - Ainayah Narul Hayatul Janah; Evan Jaelani (Indonesian Interdisciplinary Journal of Sharia Economics (IIJSE), 2026)
This study aims to analyze the influence of service quality and promotion on Instagram on the public’s decision-making regarding hospital selection in West Java. In the era of digital transformation, hospitals are required to optimize modern communication strategies to maintain their presence amid intense competition in the healthcare industry. The research method used was a quantitative survey with a cross-sectional approach. Data were collected through a structured questionnaire administered to 200 respondents residing in West Java using purposive sampling. Data analysis employed multiple linear regression using SPSS software. The results indicate that, simultaneously, service quality and Instagram promotion significantly influence public decision-making by 70.9%. Partially, service quality has a more dominant influence than Instagram promotion in determining public decisions. These findings indicate that while visual content and digital interactions are important for attracting interest, patient trust remains rooted in the excellence of physical and medical services. It is recommended that hospital management integrate high-quality service standards with educational digital marketing strategies to strengthen competitiveness in the healthcare services market.